2001
DOI: 10.1002/1521-3765(20011001)7:19<4066::aid-chem4066>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Alkoxides in Catalysis

Abstract: This paper presents recent advances in the reactions catalyzed by zirconium alkoxide. Catalytic asymmetric reactions with chiral zirconium catalysts and redox reactions are first discussed. The diverse characteristics of zirconium alkoxides as Lewis acids, Brönsted bases, and nucleophiles, are key for promoting these unique reactions. Our recent development of novel reactions, one-pot synthesis of trans-1.2-diol derivatives and trans-beta-cyanohydrins from olefins, is also described. These reactions cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Shibasaki and his co-workers reported the Zr-catalyzed domino epoxydation-nucleophilic ring opening reaction to give b-cyanohydrin 104 from cyclohexene in the presence of triphenylphosphine oxide (Scheme 33). [56] Mechanistic studies have revealed that a complex of a Zr catalyst and the phosphine oxide would change the molecular structure at each stage of the reaction by interacting with the corresponding reactants, such as bis(trimethylsilyl)peroxide (BTSP) and TMSCN.…”
Section: Domino Amine-amine Reactions In Auto-tandem Catalysismentioning
confidence: 99%
“…Shibasaki and his co-workers reported the Zr-catalyzed domino epoxydation-nucleophilic ring opening reaction to give b-cyanohydrin 104 from cyclohexene in the presence of triphenylphosphine oxide (Scheme 33). [56] Mechanistic studies have revealed that a complex of a Zr catalyst and the phosphine oxide would change the molecular structure at each stage of the reaction by interacting with the corresponding reactants, such as bis(trimethylsilyl)peroxide (BTSP) and TMSCN.…”
Section: Domino Amine-amine Reactions In Auto-tandem Catalysismentioning
confidence: 99%
“…Metal alkoxides have been applied successfully in particular to promote several organic reactions as catalysts in the polymerization of olefins and lactones [4][5][6]. Strong Lewis bases, such as alkoxides of alkaline metals, aluminium and lanthanides, have been shown to be highly active in the polymerization of such monomers as lactones, lactams and epoxides [7].…”
mentioning
confidence: 99%
“…For example, with the N‐benzyl substrate 7 c , the hexahydrocarbazole 8 c is obtained in 82 % yield, 5:1 d.r., and 86 % ee (major diastereomer) when 2,6‐dibromophenol is used as the stoichiometric proton source (entry 11). To the best of our knowledge, this is the first example of a chiral diol⋅ZrCl 4 complex acting as a chiral Lewis‐acid‐assisted Brønsted acid catalyst for a highly enantioselective reaction …”
Section: Methodsmentioning
confidence: 98%
“…A screen of additional Lewis acids revealed that ZrCl 4 provides a slightly higher yield of 8 , although the major diastereomer ( 8 a ) was produced with a lower ee value. Notably, Zr(O t Bu) 4 and related metal alkoxides failed to catalyze the reaction . A further survey of alternate chiral diols in combination with ZrCl 4 determined that ( R )‐3,3′‐dibromo‐BINOL ( L3 ) delivers the hexahydrocarbazole 8 in 40 % yield and 7:1 d.r.…”
Section: Methodsmentioning
confidence: 99%